Peningkatan Indeks Pembangunan Manusia (IPM) Melalui Pelatihan Tutor Matematika Pusat Kegiatan Belajar Masyarakat (PKBM) Kabupaten Takalar - Amir Kamal Amir; Andi Galsan Mahie; Aidawayati Rangkuti; Firman Firman; Muh. Nur; Hendra Hendra (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
The training activity which was attended by mathematics teachers who were members of the partner group of the Subject Teacher Consultation (MGMP) of Takalar Regency used information technology in the form of a smartphone application as an alternative to improving the quality of student learning in schools. There are six smartphone applications that are trained for teachers as a first step in getting to know various other applications, namely Math Tricks, Math Expert, Mathematics Dictionary, Malmath, Photomath, and Freaking Math. The six applications are contained in the training manual which is distributed to each participant before the training materials are presented .The output of this training is that teachers can master applications that are suitable to be applied in their respective school environments to facilitate the learning process.